Le rôle du mode de régulation politique états-unien dans le déclenchement de la crise économique - Éric Lahille (Revue de la Régulation)
This article, based on a critical “regulationnist” viewpoint on the role and place of politics in social dynamics, shows that the subprime crisis is also political in nature. It puts forward a theoretical interpretation focused on the logic of political “regulation” and the dynamics of the world order. Based on factual observation this approach shows the centrality of geopolitical factors in the transformation of the regulation modes of post 9/11 American policy. The “neo-conservative approach”, characterized by a particular form of neoliberalism coupled with the quest for imperial hegemony, has thus changed institutional arrangements and socio-economic strategy. This transformation in the nature of public policy and the “autonomization” of the economic sphere is in line with new political alliances between social groups which have, thus, led to a “major crisis” illustrating the inherent internal contradictions in American political regulation.